الجوانب الأخلاقية والتربوية في شعر أبي فراس الحمداني في أسر الروم دراسة وصفية بلاغية (320-357هـ): he ethical and educational aspects of Abu Firas al-Hamdani's poetry in The Roman Families Rhetorical descriptive study (320-357H) - Ayoub Osman, Abdul Sattar Abdul Wahab (SIBAWAYH Arabic Language and Education, 2020)
This research shows us the morals and educational aspects in the poetry of abi firas al-hamdani in the prison of Byzantium the research consists of three chapters as follows: The first chapter includes translation for the life of abi firas al- hamdani since his birthday until his assisnation in the year of three hundred and fifty seven in the fourth century of higrah. The second chapter includes the morals and educational aspects in the poetry of abi firas al-ham dani such as: Honoring ones parents- patience – courage-fulfillment-patriotism –trust in god and so on. The third chapter in cludes texts of study in the sector of rhetoric and criticism then the research proved that the poet had succeeded in all texts of study because he was having emotional experience and achieved organic unity and used the rhetorical methods. At the end of the study the research urges all students of knowledge to do their best and read the more about abi firas al-hamdani especially his divan because it has so many morals and educational aspects.